The SNARE Protein CfVam7 Is Required for Growth, Endoplasmic Reticulum Stress Response, and Pathogenicity of Colletotrichum fructicola - Li, Sizheng; Zhang, Shengpei; Li, Bing; Li, He (Frontiers in Microbiology, 2021)
The tea-oil tree Camellia oleifera is native to China and is cultivated in many parts of southern China. This plant has been grown for over two thousand years, mainly for its high-quality cooking oil. Anthracnose is the main disease of tea-oil tree and results in a huge loss annually. Colletotrichum fructicola is a major pathogen causing anthracnose on tea-oil tree. In previous study, we characterized that the bZIP transcription factor CfHac1 controlled the development and pathogenicity of C. fructicola. Here, we identified and characterized the function of CfVAM7 gene, which was significant down-regulated at transcriptional level in the ΔCfhac1 strain under dithiothreitol stress. Targeted gene deletion revealed that CfVam7 is important in growth, pathogenicity and responses to endoplasmic reticulum related stresses. Further analysis revealed that CfVam7 is required for appressorium formation, homotypic vacuole fusion, which important for fungal pathogen invasion. Cytological examinations revealed that CfVam7 is localized to vacuole membranes in the hyphae stage. The PX (Phox homology) and SNARE domains of CfVam7 were indispensable for normal cellular localization and biological function. Taken together, our results suggested that CfVam7-mediated vacuole membrane fusion promotes growth, stress response and pathogenicity of C. fructicola.